Evaluating the recreation potential of Ilgaz Mountain National Park in Turkey - Cetin, Mehmet; Sevik, Hakan (Springer Science and Business Media LLC, 2015)
In recent years, natural areas have become a preferred recreation area for people looking to escape their busy urban lives. The world has become so complicated that people now seek solace in areas of nature. Recreational activities conducted in natural areas, such as Ilgaz Mountain National Park, should be respectful of the environment to ensure balance and no negative environmental impact. This balance should safeguard environmental protection and only be used with the right to establish recreation planning. National parks are protected areas where the most beautiful wonders of nature exist. Thus, urban planning for recreation, and demand for recreation areas, must demonstrate both the potential of recreation resources and the protection of Ilgaz Mountain National Park. Urban open and green spaces have an important function, and in this study, it has been looked at Ilgaz Mountain National Park to examine the current situation. The aim of this study is to ensure the sustainability of natural and cultural resources via an evaluation to reveal the necessary practices and precautions regarding the area's recreational potential. As a result, Ilgaz Mountain National Park's recreation potential was found to be 72 %, and thus, it is considered to be an area of high recreation potential.
Keywords: Conservation of Natural Resources; Turkey; Parks, Recreational; Humans; Recreation; Environmental Monitoring; 13. Climate action; 11. Sustainability; 15. Life on land